A finding with a diagnosis: I just can't put my finger on it. (22nd December 2014) - Lambe, Gerard; Le, Patricia; Clay, Timothy D
Abstract : A 72-year-old man with metastatic squamous cell carcinoma of the lung presents with new lesions in the distal phalanx of right fifth finger (painful) and left great toe (painless due to long-standing peripheral neuropathy). Initially a complication of cytotoxic chemotherapy is considered and a dermatological opinion is requested. Enlargement of the lesions over the space of a week leads to plain X-ray, with findings of destruction of the distal phalanx of the involved digits confirming metastatic disease. Palliative radiotherapy is administered to decrease pain and reduce the likelihood of cutaneous and infectious complications. The patient died from systemic disease progression soon after finishing his radiotherapy. Digital metastasis (acrometastasis) should be considered by clinicians in the workup of patients with persistent digital symptoms, particularly in those with known cancer or those at high risk of cancer.